Oxidation behavior of a novel nickel-based single crystal superalloy at elevated temperature. (May 2020) - Tan, Z.H.; Wang, X.G.; Song, W.; Yang, Y.H.; Liu, J.L.; Liu, J.D.; Yang, L.; Zhou, Y.Z.; Sun, X.F.
Abstract: The oxidation behavior of a novel low-cost single crystal superalloy was thoroughly studied at high temperature. Three distinctive stages were observed in the oxidation kinetics curve, which corresponded to the different oxide film structures and oxidation mechanisms. The outer NiO grains, several spinels as well as inner Al2 O3 layer took shape at first stage while the oxidation dynamics obeyed cubic law. However, the NiO particles began to spall off the specimen surface and the continuity of Al2 O3 layer was partly destroyed in the next several hours. The alloy went through severe oxidation weight gaining at second stage which could be rationalized by the severe oxidation of W and Mo. The non-protective NiWO4 and NiMoO4 spinels were surprisingly found and the Al2 O3 particles demonstrated the rod-like morphology during this period. The re-formation of dense Al2 O3 layer and the volatilization of MoO3 gave rise to the reduction of mass gaining rate in the final stage, additionally, the oxidation kinetics transformed to subparabolic characteristic. Moreover, the experimental alloy exhibited good microstructural stability at elevated temperature, however, the microstructure degradation was considerably serious. The entire thickness of γ′-free layers had exceeded 0.1 mm on the alloy surface after 200 h oxidation at 1120 °C. Highlights: The oxidation mechanism and microstructure degradation of a novel low-cost single crystal superalloy were studied. The oxidation kinetics exhibited three distinctive stages which corresponded to different oxidation films and mechanisms. The NiWO4 and NiMoO4 spinels were surprisingly detected which rationalized the dramatic oxidation weight gaining. The continuous and discontious Al2 O3 layers as well as rod-like Al2 O3 particles were found at different stages.